Verbal and Visual Communication in the Movie The Hunger Games - Fridayanti, Ayu Putu (Humanis; Vol 22 No 3 (2018), 2018)
Communication can be made by using two kinds of mode; they are verbal and visual communication modes. Nowadays, people tend to focus on the verbal communication and ignore the visual communication itself, even though they have the same important part of communication by using language. This study entitled “Verbal and Visual Communication in the Movie The Hunger Games” is trying to reveal and find out the sentence forms of the characters’ verbal utterances, the visual signs of the scene among the characters and the relationship between those communications. In the study, The Hunger Games movie is used as the data source. It tells about a death game that was held by a capitol city which was inhabited by people of the upper class and the people of the lower class who live in the districts as the tribute of the game. The method used to analyze the movie is Qualitative method. The main theory used is proposed by Dyer (1986) with his Verbal and Visual Communication theory and helped by using a theory from Timothy Shopen (2007) describing the types of sentence in form of verbal utterance. Based on the analysis, all of the sentence types as the verbal communication analysis and almost all of the visual sign elements in the movie were found, except for the national and racial element in appearance category. The verbal and visual communications represented in the movie supports each other to convey the meaning. It shows the differences between two different social classes; they are upper and lower classes. How the characters of the upper class speak, act, and look, tend to be more polite, prestigious, classy, colorful, and more educated than the characters of the lower class. It shows the relationship of visual and verbal communication itself.